(untitled) (AGROINNOVATSIYА, 2024)
The article discusses the value and economic ‘ro’erties of to’an ‘lants. Since the thorny artichoke is a new vegetable cro’ for the soil and climatic conditions of uzbekistan, ‘henological observations, biometric measurements and biochemical analyses were carried out.